Self-Processing and Self-Face Reaction Time Latencies: A Review - Gordon G. Gallup (MDPI AG, 2021)
In this article, we detail the advantages of self-face identification latencies over more traditional tests of mirror self-recognition. Using reaction time latencies (measured in milliseconds) to identify different dimensions of the self, instead of relying on a simple dichotomous pass/fail mirror mark-test outcome, enables investigators to examine individual differences in self-processing time. This is a significant methodological step forward with important implications. The point of departure for our article is to detail research we and others have conducted on latencies for self-face identification, to show how self-processing occurs in the right side of the brain, how schizophrenia is a self-processing disorder, how self-face reaction time latencies implicate the existence of an underlying multiple modal self-processing system, and to explore ideas for future research.